A cluster randomised controlled trial of a brief couple-focused psychoeducational intervention to prevent common postnatal mental disorders among women: study protocol. Issue 9 (23rd September 2014) - Rowe, Heather; Wynter, Karen; Lorgelly, Paula; Amir, Lisa H; Ranasinha, Sanjeeva; Proimos, Jenny; Cann, Warren; Hiscock, Harriet; Bayer, Jordana; Burns, Joanna; Ride, Jemimah; Bobevski, Irene; et al.
Abstract : Introduction: Postnatal common mental disorders among women are an important public health problem internationally. Interventions to prevent postnatal depression have had limited success. What Were We Thinking (WWWT) is a structured, gender-informed, psychoeducational group programme for parents and their first infant that addresses two modifiable risks to postnatal mental health. This paper describes the protocol for a cluster randomised controlled trial to test the clinical effectiveness and cost-effectiveness of WWWT when implemented in usual primary care. Methods and analysis: 48 maternal and child health (MCH) centres from six diverse Local Government Areas, in Victoria, Australia are randomly allocated to the intervention group (usual care plus WWWT ) or the control group (usual care). The required sample size is 184 women in each group. English-speaking primiparous women receiving postpartum healthcare in participating MCH centres complete two computer-assisted telephone interviews: baseline at 4 weeks and outcome at 6 months postpartum. Women attending intervention MCH centres are invited to attend WWWT in addition to usual care. The primary outcome is meeting Diagnostic and Statistical Manual-IV (DSM-IV) diagnostic criteria for major depressive episode; generalised anxiety disorder; panic disorder with or without agoraphobia, agoraphobia with or without panic, social phobia, adult separation anxiety or adjustment disorder with depressed mood, anxiety or mixed depressed mood and anxiety within the past 30 days at 6 months postpartum. Secondary outcomes are self-rated general and emotional health, infant sleep problems, method of infant feeding, quality of mother–infant relationship and intimate partner relationship, and healthcare costs and outcomes. Ethics and dissemination: Approval to conduct the study has been granted. A comprehensive dissemination plan has been devised. Trial registration number: Australian New Zealand Clinical Trials Registry ACTRN12613000506796. UTN: U1111-1125-8208.